2018
DOI: 10.1155/2018/2308619
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii-Induced Long-Term Changes in the Upper Intestinal Microflora during the Chronic Stage of Infection

Abstract: Toxoplasma gondii is an obligate intracellular parasite with worldwide distribution. Felines are the definitive hosts supporting the complete life cycle of T. gondii. However, other warm-blooded animals such as rodents and humans can also be infected. Infection of such secondary hosts results in long-term infection characterized by the presence of tissue cysts in the brain and other organs. While it is known that T. gondii infection in rodents is associated with behavioral changes, the mechanisms behind these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
1
8
1
Order By: Relevance
“…Our results contrast with those of Shao et al (2020) and Prandovszky et al (2018), who reported substantial changes in the overall bacterial community composition in the gastrointestinal tract of mice chronically infected with Toxoplasma . These differences in results may be driven by the differing impacts of Toxoplasma infection in mice compared to rats and the implications infection has for sustained inflammation in each species.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contrast with those of Shao et al (2020) and Prandovszky et al (2018), who reported substantial changes in the overall bacterial community composition in the gastrointestinal tract of mice chronically infected with Toxoplasma . These differences in results may be driven by the differing impacts of Toxoplasma infection in mice compared to rats and the implications infection has for sustained inflammation in each species.…”
Section: Discussioncontrasting
confidence: 99%
“…Infectious agents, such as Toxoplasma gondii, have been suggested to contribute to the development of schizophrenia (107,108). It has been recently demonstrated in a preclinical study that chronic Toxoplasma gondii infection results in an enrichment of Bacteroidetes in CD1 mice compared to noninfected controls (109). Interestingly, Bacteroidetes were also increased in a pharmacological model of schizophrenia (52) and in individuals with chronic schizophrenia (57).…”
Section: Infectious Agentsmentioning
confidence: 99%
“…Toxoplasma gondii ( T. gondii ), a vital obligate intracellular parasitic protozoan, is the causative agent of toxoplasmosis (Kato, 2018). The characteristics of it are worldwide distribution and broad host range that can infect all warm‐blooded animals including humans (Prandovszky et al ., 2018; Coutermarsh‐Ott, 2019). T. gondii is considered as a considerably successful parasitic organism, which can persist in the host for the host's entire lifetime and present opportunistic pathogenicity after successful infection (Dubey and Jones, 2008; Montazeri et al ., 2018a,b).…”
Section: Introductionmentioning
confidence: 99%